Comparison of Chlorophyll-a Concentrations Before and After Tsunami. Case study: Palu Bay, Central Sulawesi - Muhammad Renaldi Apriansyah; Shinta Septiantina; Acep Saepul Zamil; Della Ayu Lestari; Wildan Aprizal Arifin (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Chlorophyll-a is an indicator of the abundance of phytoplankton in the waters that play a role in the photosynthesis process. Chlorophyll-a measurement can be done in two ways, namely conventional and the use of remote sensing technology. This research method utilizes remote sensing technology Landsat 8 imagery processed using ER Mapper 7.1 software. The purpose of this study is to inform the comparison of chlorophyll-a before and after the tsunami disaster in the waters of Palu Bay, Central Sulawesi Province. The results showed that these waters had increased the abundance of phytoplankton after the tsunami disaster.